What Drives Growing Currency Co-movements with the Renminbi? - Bokyeong Park; Jiyoun An (East Asian Economic Review (EAER), 2020)
China's increasing trade volume and continuous integration with global financial markets have strengthened the influences of the renminbi on the exchange rates of different currencies. Previous studies find closer co-movements between the renminbi and other currencies. This paper is novel to investigate the underlying determinants of the comovement further, using panel data of over thirty-four countries. Our results show that stronger bilateral trade and financial linkages with China have a positive association with the currency co-movement. Moreover, countries with greater flexibility in exchange rate regimes show stronger co-movements. These findings imply that growing co-movements are the consequence of autonomous decisions at the market rather than that of management by governments or central banks.
Keywords: F31; F33; F36; 330; Currency Co-movements; Renminbi; Trade Linkage; Financial Linkage; Exchange Rate Regime